2007
DOI: 10.1016/j.biomaterials.2006.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Adult adipose-derived stem cell attachment to biomaterials

Abstract: Attachment of adipose-derived stem cells (ASC) to biomaterials prior to implantation is a possible strategy for mediating inflammation and wound healing. In this study, the ASC percent coverage was measured on common medical grade biosensor materials subjected to different surface treatments. Cell coverage on silicone elastomer (poly dimethylsiloxane) was below 20% for all surface treatments. Polyimide (Kapton), polyurethane (Pellethane) and tissue culture polystyrene all exhibited >50% coverage for surfaces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 13 publications
1
34
0
1
Order By: Relevance
“…This result could be explained by the high affinity of stem cells for TCPS. 39,40 Similar studies showed no significant proliferation difference between TCPS and fibronectin coating. 40 Hence, dASC behave differently from primary SC, which show enhanced proliferation on fibronectin and laminin.…”
Section: Ecm Does Not Influence Proliferation Of Dascmentioning
confidence: 58%
See 1 more Smart Citation
“…This result could be explained by the high affinity of stem cells for TCPS. 39,40 Similar studies showed no significant proliferation difference between TCPS and fibronectin coating. 40 Hence, dASC behave differently from primary SC, which show enhanced proliferation on fibronectin and laminin.…”
Section: Ecm Does Not Influence Proliferation Of Dascmentioning
confidence: 58%
“…39,40 Similar studies showed no significant proliferation difference between TCPS and fibronectin coating. 40 Hence, dASC behave differently from primary SC, which show enhanced proliferation on fibronectin and laminin. 34,41 ECM molecules protect dASC from induced apoptosis and anoikis Cell adhesion to ECM is important for survival, differentiation, and migration of cells, 16 and cell attachment to biomaterials and survival is important for regenerative cell therapy.…”
Section: Ecm Does Not Influence Proliferation Of Dascmentioning
confidence: 58%
“…In the first method, two embossed polystyrene parts were treated with oxygen plasma (Prichard et al 2007) using a Technics Microstripper, with a setting of 100 W and 100 mTorr O 2 pressure for 1 min. The treated surfaces were placed in contact, and the channels were aligned with the aid of an optical microscope.…”
Section: Polystyrene Layer Bondingmentioning
confidence: 99%
“…Many studies have combined biomaterial scaffolds with ASCs to repair bone defects, for example, biphasic calcium phosphate nanocomposite (NanoBCP) (102), poly (lactic-co-glycolic acid) (PLGA) (103), HA/tricalcium phosphate (TCP) (104), chitooligosaccharide (COS) (105), fibrin/HA (106), and so on. Prichard et al (107) examined cell coverage and cell function of ASCs on different biomaterials, including fibronectin, silicone rubber, dualligand, polyimide, oxygen plasma plus fibronectin and polyurethane. The results showed that cell attachment was very strong on both polyurethane and polyimide for all attachment methods.…”
Section: In Vivo Studiesmentioning
confidence: 99%